INDONESIAN CHILDREN WATCHING AUSTRALIAN TELEVISIONS: AN ETHNOGRAPHIC STUDY - Antar Venus (Universitas Padjadjaran, 2001)
This study is concerned with 'the way children watching television' while focusing on the context of viewing activities, not on the program content. The study was conducted in Sydney Australia for six weeks from September to November 1998. For the purpose of the research, two Indonesian children had been chosen as the informants. The ethnographic method employed in this study due to the reasons that the context of children interacting with television cannot be quantified. In addition, data for the research have to be obtained in a natural environment where children do their usual viewing activities. The research findings shows that the observed children watched TV in an active and critical way. They are used to giving reasonable responses to any programs shown on television. Keywords : Ethnography, natural setting, Viewing activities